Intracranial Hemorrhages on Extracorporeal Membrane Oxygenation: Differences Between COVID-19 and Other Viral Acute Respiratory Distress Syndrome. Issue 6 (12th January 2022) - Seeliger, Benjamin; Doebler, Michael; Hofmaenner, Daniel Andrea; Wendel-Garcia, Pedro D.; Schuepbach, Reto A.; Schmidt, Julius J.; Welte, Tobias; Hoeper, Marius M.; Gillmann, Hans-Jörg; Kuehn, Christian; Ehrentraut, Stefan Felix; Schewe, Jens-Christian; et al.
Abstract : OBJECTIVES: Extracorporeal membrane oxygenation (ECMO) is a potentially lifesaving procedure in acute respiratory distress syndrome (ARDS) due to COVID-19. Previous studies have shown a high prevalence of clinically silent cerebral microbleeds in patients with COVID-19. Based on this fact, together with the hemotrauma and the requirement of therapeutic anticoagulation on ECMO support, we hypothesized an increased risk of intracranial hemorrhages (ICHs). We analyzed ICH occurrence rate, circumstances and clinical outcome in patients that received ECMO support due to COVID-19–induced ARDS in comparison to viral non-COVID-19–induced ARDS intracerebral hemorrhage. DESIGN: Multicenter, retrospective analysis between January 2010 and May 2021. SETTING: Three tertiary care ECMO centers in Germany and Switzerland. PATIENTS: Two-hundred ten ARDS patients on ECMO support (COVID-19, n = 142 vs viral non-COVID, n = 68). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Evaluation of ICH occurrence rate, parameters of coagulation and anticoagulation strategies, inflammation, and ICU survival. COVID-19 and non-COVID-19 ARDS patients showed comparable disease severity regarding Sequential Organ Failure Assessment score, while the oxygenation index before ECMO cannulation was higher in the COVID group (82 vs 65 mm Hg). Overall, ICH of any severity occurred in 29 of 142 COVID-19 patients (20%) versus four of 68 patients in the control ECMO group (6%). Fifteen of those 29 ICH events in the COVID-19 group were classified as major (52%) including nine fatal cases (9/29, 31%). In the control group, there was only one major ICH event (1/4, 25%). The adjusted subhazard ratio for the occurrence of an ICH in the COVID-19 group was 5.82 (97.5% CI, 1.9–17.8; p = 0.002). The overall ICU mortality in the presence of ICH of any severity was 88%. CONCLUSIONS: This retrospective multicenter analysis showed a six-fold increased adjusted risk for ICH and a 3.5-fold increased incidence of ICH in COVID-19 patients on ECMO. Prospective studies are needed to confirm this observation and to determine whether the bleeding risk can be reduced by adjusting anticoagulation strategies.